If Not Now, When? : Short-Cycle Programs in Latin America - Ferreyra, Maria (International Higher Education, 2021)
Higher education in Latin America and the Caribbean (LAC) has expanded dramatically in the new millennium, yet enrollment in short-cycle programs (SCPs) is still relatively low. Recent evidence indicates that while SCPs generate, on average, good labor market outcomes, they vary greatly in quality. Further, SCP providers respond rapidly and flexibly to local economy needs. Specific practices related to faculty, job search assistance, and interaction with prospective employers are distinctive of the best programs.